Analisis Struktur Kekuatan Persaingan Dan Cluster Industri - Feriadi Feriadi; Jasmine Damayanti; Muhammad Yasin (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
This research aims to analyze the structure of competitive forces and industrial clusters. Using Porter's five forces model framework, this research evaluates the key elements that influence competitiveness in a particular industry. This study also utilizes an industrial cluster approach to understand the dynamics of groups of companies operating in the same or related sectors. The research results show that factors such as the threat of new entrants, the bargaining power of suppliers, the bargaining power of buyers, the threat of substitute products, and competition between companies have a significant role in determining the structure of competition. In addition, industrial cluster analysis shows that synergy between companies in a cluster can increase operational efficiency and innovation, thereby strengthening competitive positions in the market. It is hoped that these findings will provide insight for companies and policy makers to formulate effective strategies in facing competition and exploiting the potential of industrial clusters.